The Effects of Exclusive Walking on Lipids and Lipoproteins in Women with Overweight and Obesity: A Systematic Review and Meta-Analysis. Issue 2 (February 2022) - Ballard, Anjulyn M.; Davis, Ashlee; Wong, Brett; Lyn, Rodney; Thompson, Walter R.
Objective: To evaluate the effects of walking, independent of diet and weight-loss, on lipids and lipoproteins in women with overweight and obesity. Data Source: Academic Search Complete, Alternative Health Watch, Global Health, Health Source, CINAHL, MEDLINE, EMBASE, SportDiscus, and ProQuest. Study Inclusion and Exclusion Criteria: (1) experiment-control design; (2) women with overweight or obesity; (3) walking as the experiment's independent variable; (4) four or more weeks; and (5) pre- to post-assessment of lipids and/or lipoproteins. Excluded studies reported use of lipid-lowering medication, diet or other modes of physical activity, and alternative interventions as the control. Data Extraction: Data extraction and study quality were completed by the first 2 authors using the Cochrane review protocol and risk of bias assessment. Data Synthesis: Raw mean difference between the experiment and control groups using a random effects model. Results: Meta-analyses of 21 interventions (N = 1129) demonstrated exclusive walking improves total cholesterol (raw mean difference = 6.67 mg/dL, P = .04) and low-density lipoproteins (raw mean difference = 7.38 mg/dL, P = .04). Greater improvement in total cholesterol, triglycerides, high-density lipoproteins, and low-density lipoproteins existed in women with obesity. Conclusions: Exclusive walking aids in normalizing total cholesterol and LDLs in women with overweight and obesity. Exclusive walking can be used as a non-pharmacologic therapy, which may have positive clinical outcomes for individuals who especially struggle with diet and weight-reduction.